Innovative applications of Mo(W)-based catalysts in the petroleum and chemical industry : emerging research and opportunities - Ge, Hui, 1964- (Advances in chemical and materials engineering (ACME) book series., 2017)
"This book explores the advances in synthesis and catalytic application of 2D layer Mo(W) dichalcogenides and the traditional Mo(W)S2 based catalysts with a focus on the newly insight of their atomic active structures and reaction mechanism, and show how the Mo(W)S2 based catalysts have been improved based on the renewed knowledge and novel synthesizing technique"--